Upaya Guru Pendidikan Agama Islam dalam Meningkatkan Pemahaman Keagamaan Siswa - Jafri Jafri (Program Studi Pendidikan Agama Islam STAI Auliaurrasyidin Tembilahan, 2021)
This study aimed to determine the efforts of Islamic Religious Education teachers in improving students' religious understanding at SMA Negeri 1 Tembilahan. The approach in this study was a descriptive qualitative approach using observation, interviews, and documentation. Data analysis techniques were data reduction, data presentation, and data verification while checking the validity of the data was expanded participation, observing accuracy, triangulation, and expert consultation. The results showed that teachers had implemented well except for the lack of infrastructure and learning time in optimizing students' religious understanding. Based on this research, the practical implications were used as material to assist teachers in optimizing and new knowledge for teachers so that teachers can improve students' religious understanding.